LC-MS analysis and antioxidant, antibacterial, and antidiabetic activity of Jumli Marshi rice from Nepal: An in vitro and in silico investigation to validate their potential as a functional food - Ram Kishor Yadav; Rekha Bhandari; Harish Babu P C; Prabhat Kumar Jha; Bipindra Pandey; Sindhu KC; Siddha Raj Upadhaya; Sushil Panta; Sajan Lal Shyaula; Khem Raj Joshi (PLoS ONE, 2025)
Jumli Marshi (J. Marshi), a native rice cultivar in Nepal, is gaining popularity owing to its health benefits for obesity, hypertension, and diabetes. However, scientific evidence verifying its therapeutic potential is lacking until November 2024. Therefore, we aimed to characterize the phytoconstituents and evaluate the antioxidant, antibacterial, and antidiabetic properties of J. Marshi, along with its ADME toxicity profile, using both in vitro and in silico approaches. Liquid chromatography-mass spectrometry analysis of a 70% methanol extract from J. Marshi identified ten plant-based compounds, including phenolic acids, flavonoids, and γ-oryzanol. The extract exhibited significant antioxidant properties, neutralizing DPPH free radicals with a fifty-percentage inhibitory concentration (IC50) of 42.65 ± 3.9 µg/mL, compared to ascorbic acid’s IC50 of 4.12 ± 0.7 µg/mL. It also showed antibacterial activity against Staphylococcus aureus, with a zone of inhibition (ZOI) ranging from 7 to 11 mm and a minimum inhibitory concentration (MIC) of 1.56 mg/mL, compared to standard antibiotics meropenem (ZOI: 24 ± 1.6 mm; MIC: 1.56 mg/mL). The enzymatic assay demonstrated that the J. Marshi extract inhibits fifty percent of enzyme activity at a concentration (EC50) of > 1000 µg/mL for α-amylase and 250 ± 2.5 µg/mL for α-glucosidase, in contrast to the standard acarbose, exhibiting an EC50 of 35.5 ± 1.5 µg/mL for α-amylase and 189.5 ± 1.9 µg/mL for α-glucosidase. In silico docking studies revealed strong interactions of rice phytoconstituents with target protein catalytic residues, particularly gamma-oryzanol for α-amylase (−10.0 kcal/mol) and chlorogenic acid for α-glucosidase (−7.7 kcal/mol), compared to acarbose (−6.9 to −7.1 kcal/mol). ADME toxicity analysis suggested that tricin and gamma-oryzanol had the best drug-likeness and safety profiles. To our knowledge, this is the first study to reveal the presence of bioactive phenolic acids and flavonoids. Furthermore, it offers scientific evidence supporting significant antioxidant and α-glucosidase-inhibitory properties, confirming the potential applications of J. Marshi rice as a functional food used for the management of diabetes.